Pengaruh Jarak Daerah Penangkapan Ikan Terhadap Hasil Tangkapan Payang yang Beroperasi di Perairan Teluk Staring Kabupaten Konawe Selatan - Dita Safitri; Muslim Tadjuddah; Ahmad Mustafa; Naslina Alimina; Hasnia Arami (Universitas Halu Oleo, 2022)
The main catch of payang fishing gear operating in the waters of Staring Bay is small pelagic fish. The distribution of fish resources starts from shallow coastal waters to offshore so it is suspected that the size of the catch length varies greatly based on the distance of the fishing area. The purpose of this study was to determine the composition of the length of the catch and determine the relationship between the distance of the fishing grounds and the length of the fish caught by the payang fishing gear in the waters of Staring Bay, South Konawe Regency. This research was conducted in December-January 2022 in the waters of Staring Bay, South Konawe Regency. The analysis method consists of analysis of the composition of the size of the catch, correlation analysis and determination. The results showed that the composition of payang catches in the waters of the Gulf was dominated by indian mackerel with a length of 6.2-17.5 cmFL, and a length of shortfin scad was 6.3-17.5 cmFL. The results of the analysis showed that the relationship of the distance of the fishing grounds both from the nearest land and from the fishing base to the size of the length of the fish caught in the waters of Staring Bay showed a strong correlation. The suggestion of this study is the need for further research on the size of the dominant catch.